Streptokinase@alumina nanoparticles as a promising thrombolytic colloid with prolonged action. Issue 35 (22nd August 2016) - Chapurina, Yulia E.; Drozdov, Andrey S.; Popov, Inna; Vinogradov, Vasiliy V.; Dudanov, Ivan P.; Vinogradov, Vladimir V.
Abstract : A fully biocompatible thrombolytic nanocolloid providing high stability and prolonged activity has been developed. Abstract : The present study is devoted to the development of a new class of thrombolytic systems – nanocolloids. A non-direct plasminogen activator, streptokinase, was entrapped in a sol–gel matrix based on boehmite nanoparticles used in medical practice as the most common vaccine adjuvant. It is shown that when the enzyme content in the composite is less than 10%, only minor release is observed, while thrombolytic properties are maintained at a relatively high level, demonstrating the prolonged effect. Based on the obtained composites, thrombolytic nanocolloids containing nanoparticles of less than 500 nm size and suitable for parenteral administration were produced. The thrombolytic properties were studied using the plasminogen activation tests, human plasma clots and a model thrombus made from a whole human blood. Based on the obtained results, the structure of the composites and the mechanism of their action are suggested.